TECHNOLOGICAL ASPECTS OF ACCOUNTING AUTOMATION SYSTEM AS A DECISION SUPPORT SYSTEM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Nowadays all businesses need access to an extensive pool of information. Reporting, financial and accounting analysis, financial planning and budgeting are key factors for market-oriented corporate management and successful business. In the digital economy, strong competition, responsible entrepreneurship and corporate social responsibility the business feels a need for revolution and new decision sciences for complex systems that collect big data, analyze it and create reports that can be used by managers for decision-making. The present study aims to prove that the accounting automation system is an important tool for managing the economic activity of companies, because it mediates the interrelationships between managers/decision-makers, or subjects of management, economic activity and its results, or object of management, in support of Business intelligence, or BI, Data and Analysis, Power Platform, etc. The following research tasks have to be settled for reaching the above-mentioned goal: 1. to analyze the components of decision support systems; 2. to research the types of decision support systems; 3. to demonstrate the impact of the accounting automation system as a decision support system on the optimization and improvement of the working processes and making adequate timely management decisions; 4. to analyze the technological aspects of accounting automation system as a decision support system; 5. to research the challenges and solutions regarding ERP systems and SAP. In the course of the study shall be justified the thesis that the successful business is based on true, accurate and reliable information which is mostly generated by automated accounting system as a decision support system and contemporary information technologies. The results of the research are expressed in establishing the way to ensure and guarantee the unification, acceleration and optimization of the input-processing-output process, analysis, financial modelling, financial planning, etc. about decision support and respectively wealth management.